Encyclopedia of the Harlem Renaissance - Aberjhani (Facts on File library of American history, 2003)
Contains approximately 370 alphabetically arranged entries covering the emergence of new ideas in literature, political thought, civil rights, racial pride, and the arts during New York City's Harlem Renaissance in the 1920s and 1930s.